Agrobacterium tumefaciens-mediated transformation of common bean (Phaseolus vulgaris) var. Brunca - Solís-Ramos, Laura-Yesenia; Ortiz-Pavón, Julio-César; Andrade-Torres, Antonio; Porras-Murillo, Romano; Brenes-Angulo, Arturo; Castaño de la Serna, Enrique (Revista de Biología Tropical, 2019)
Common bean is a crop recalcitrant to in vitro regeneration and therefore it lacks an efficient transformation protocol that can be reproduced using A. tumefaciens. The main goal of this study was to establish a protocol for A. tumefaciens mediated transformation of Phaseolus vulgaris var. Brunca by marker genes (gusA and nptII) together with the gene for trehalose-6-phosphate synthase from Saccharomyces cerevisiae (TPS1) used in other species to increase tolerance to abiotic stress. The β-glucuronidase activity was detected in 45 % of the LBA4404 ElectroMAX® pCAMBIA1301 infected explants. Transformed explants regenerated new shoots after four to five months period in a kanamycin rich media. Surviving plants were evaluated by PCR and presented an 0.5 % efficiency of transformation. The established protocol for genetic transformation of common bean has two additional advantages with respect to previous reports: (1) it allows for obtaining transformed regenerants and (2) the genetic transformation was stable for the selective gene.